Women Writers, Authorship, and the Late-Eighteenth Century Novel: Representations of the Female Author in the Minerva Press (1785 - 1800). - Davies, Colette (2022)
In this thesis, I explore a selection of female-authored novels published by the Minerva Press between 1785 and 1800. I then turn to a selection of letters written by Minerva Press female writers and sent to the Literary Fund: a charity established to support impoverished writers. Literary society scrutinised and often belittled the female author. It was widely disparaging of the popular novel as well. The Minerva texts I investigate shed light on how these women writers, often dependent financially on their pens, strategically represented their own and their characters’ literary interactions and activities during an era of transformation in the literary marketplace and social turbulence. I trace how they defined and redefined the subject position of the female author, arguing that these wide-ranging presentations provide predominantly conservative narratives about the female author and on the popular novel but that they also destabilise Romantic-period criticisms of both.